Tuhan, Manusia, dan Alam Dalam Perspektif Filsafat Pendidikan Islam - Putri, Aurora Cahyani; Maulida, Farida; Adawiyah, Siti Rabiatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In this view, God is regarded as the source of science, the foundation of the philosophy of education, and the purpose of education. Islamic education emphasize diversity, character development, and spirituality that is square because humans are viewed as special beings who have the ability to receive the Grace of God and have the freedom to choose what will be punished by god if they do something good or bad. The universe is seen as a means of knowing the existence of God, showing his existence, and giving man knowledge.